Influence of non-Newtonian blood flow models on drug deposition in the arterial wall - Gudiño, Elías (2019)
In this paper, we investigate the influence of non-Newtonian blood flow models on drug diffusion from a coronary drug-eluting-stent (DES). We consider the Oldroyd-B, Phan-Thien-Tanner (PTT) and Giesekus viscoelastic models for the description of fluid dynamics of blood. The model for blood flow is coupled with plasma filtration and mass transport from a DES. The model for the transport problem takes into consideration non-Fickian diffusion, drug dissolution, polymer degradation and binding. We propose an Implicit-Explicit (IMEX) finite element method and show numerical experiments that confirm the effectiveness and order of convergence of the employed methodology. The numerical results indicate that an increase in the elastic properties of the blood leads to an increase of the concentration of free drug in the arterial wall. Finally, we present unsteady simulations comparing the Newtonian and non-Newtonian blood flow models.